The effects of backward locomotion as part of a rehabilitation program on the functional ability of patients following knee injury - Brink, Marisa (Stellenbosch : University of Stellenbosch, 2010)
Thesis (M Sport Sc (Sport Science)--University of Stellenbosch, 2010.